New numerical method for mechanics of continuous media - Jach, Karol; Mroczkowski, Maciej; Świerczyński, Robert; Włodarczyk, Edward; Wolański, Piotr (Computer Assisted Methods in Engineering and Science, 1995)
A new, original numerical method of free particles, for mechanics of continuous media, has been developed. The free particle hydrocodes (HEFP), based on this method, are the powerful tools that can be used to simulate, in the sense of computational physics, events with very high dynamic effects. In the paper, computational simulation of several attractive and practically important problems like: processes of the detonation, high velocity impacts and hypervelocity planetary impacts, shaped charge jet formation, explosive forming of projectiles, penetrating of the armour plate, is posed. All of them include shocks, very large deformations of solids, processes of cratering with impact jets generation and targets penetration . The method of free particles is a very useful for magnetohydrodynamical (MHD) simulation, too. It is possible to simulate ideal MHD and non-ideal MHD processes, and such exemplary results are also presented. In the paper, physical, mathematical and numerical models as well as results of some complex, unsteady, spatially two-dimensional simulations are presented.